Fractional-order equations and inclusions - Fečkan, Michal; Pospíšil, Michal 1984-; Wang, JinRong (Fractional calculus in applied sciences and engineering, 2017)
This book presents fractional difference, integral, differential, evolution equations and inclusions, and discusses existence and asymptotic behavior of their solutions. Controllability and relaxed control results are obtained. Combining rigorous deduction with abundant examples, it is of interest to nonlinear science researchers using fractional equations as a tool, and physicists, mechanics researchers and engineers studying relevant topics. ContentsFractional Difference EquationsFractional Integral EquationsFractional Differential EquationsFractional Evolution Equations: ContinuedFractional Differential Inclusions